1987
DOI: 10.1073/pnas.84.10.3171
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant splicing events that are induced by proviral integration: implications for myb oncogene activation.

Abstract: Activation of the mouse c-myb oncogene in Abelson virus-induced plasmacytoid lymphosarcomas was studied using cDNA cloning and nucleotide sequence analysis. The results presented here show that viral integration in the myb locus generates splicing errors at the 5' and 3' regions. Viral integration results in transcriptional initiation within the viral long terminal repeat and generation of a chimeric mRNA that lacks the rst three coding exons. The alterations at the 3' end are caused by an aberrant splicing ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 24 publications
(33 reference statements)
5
29
0
Order By: Relevance
“…The 4.4-kb mRNA species in the other cell types was detected in the autoradiograph after 18 h of exposure as a faint smear just above the 4.0-kb band. This is consistent with the previous finding that the steady-state level of E6A-containing myb transcripts was much lower than that of the major c-myb transcript in mouse cells (34,39 expressed in Jurkat cells, suggesting that other myb-related transcripts are present in these cells. No E7A sequence was detected in the murine NFS467 cells.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The 4.4-kb mRNA species in the other cell types was detected in the autoradiograph after 18 h of exposure as a faint smear just above the 4.0-kb band. This is consistent with the previous finding that the steady-state level of E6A-containing myb transcripts was much lower than that of the major c-myb transcript in mouse cells (34,39 expressed in Jurkat cells, suggesting that other myb-related transcripts are present in these cells. No E7A sequence was detected in the murine NFS467 cells.…”
Section: Methodssupporting
confidence: 82%
“…An additional in-frame exon, termed E6A, was first identified in cDNA clones isolated from c-myb transcripts derived from one of the murine myeloid tumors that carries a provirus-disrupted c-myb allele (34). It was initially proposed that the alternative exon was used as a consequence of upstream proviral insertion, but subsequent analyses showed that the E6A exon is also present in myb transcripts expressed in normal and tumor cells which lack c-myb rearrangements (39).…”
mentioning
confidence: 99%
“…This 89-kDa protein is translated from an alternatively spliced mRNA encoded by the c-myb gene, which results in the addition of 363 bp between exons 9 and 10. This region has been designated exon 9A (50,55).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing further downstream between exons 6 and 7 of the murine c-myb transcript has been observed in normal thymus and spleen cells (34) as well as in myeloid tumor cells induced by proviral integration within the 5'-terminal region of the c-myb gene (31).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the chicken and murine c-myb genes are targets for proviral insertions that lead to hematopoietic malignancies of myeloid or B-cell origin (15,19,31,35).…”
mentioning
confidence: 99%